Cardiovascular Evaluation in Bitches in Oestrus, Pregnancy and Puerperium - Aguiar, Mayara Cristini Ferreira; Aptekmann, Karina Preising; Egert, Leandro; Reis, Afonso Cassa; Madureira, Paula; Barcellos, Márcio Paiva (Acta Scientiae Veterinariae, 2018)
Background: Pregnancy may change maternal hemodynamic, which is considered a physiological mechanism for adaptation. Cardiac output tends to be influenced by reductions in vascular resistance and increases in uterine vasculature, as well as reduced autonomic tone combined with gestational physiological anaemia and increased blood volume due to increased plasma volume and hormonal mechanisms. In bitches, few studies have been conducted investigating the changes of the system and the clinical implications for the mother and foetuses due to poor cardiac adaptation during pregnancy. Materials, Methods & Results: Systolic blood pressure (SBP), electrocardiographic and Doppler echocardiographic measurements and serum sodium (Na), potassium (K), calcium (Ca) and phosphorus (P) levels were evaluated in six bitches of reproductive age. An evaluation was performed in oestrus (M0), followed by evaluations at 25 (M1), 45 (M2), and 60 days (M3) after the last natural or artificial insemination and 15 days after delivery (M4). For the statistical analysis, the means, medians and the standard deviation were calculated. The data were analysed using ANOVA and the Tukey test, with significance level of 5%. A descriptive analysis was performed for color Doppler in echocardiogram evaluation, cardiac axis and rhythm in electrocardiogram evaluation. In the electrolytic evaluation, significant differences were found only in the serum levels of Na, noticed as a reduction in M0-M1 and M3-M2 and an increase in M1-M2 and M3-M4. No significant differences were observed in the SBP, although there was a tendency to SBP reduction. ECG parameters were not significantly different, with no rhythm or conduction disturbances. There was not a significant difference in HR. Four animals (66.6%) had axis deviation to the right when comparing the oestrous phase with the final quarter of pregnancy. The echocardiographic parameters did not show significant changes. Discussion: The reduction observed in Na can occur by salt depletion, by dilutional or metabolic mechanisms. In contrast, the elevation in Na concentration could occur as a result of fluid and electrolyte retention by kidneys during gestation. The absence of electrocardiographic changes may be justified by the stability of mean serum potassium concentrations. An increase in HR five days before the expected calving time, demonstrating the maximum cardiac activity in this gestational phase, is related by other authors, therefore, in the present study, the absence of significant change in HR can be explained by the period in which the data collection was performed, 45 days of gestation, being therefore prior to the period of greatest HR. The cardiac axis deviation can be explained by the distension of the gravid uterus that cause compression of the adjacent organs, leading to diaphragmatic compression and consequent repositioning of the thoracic structures. A tendency to SBP reduction observed is directly influenced by peripheral vascular resistance and cardiac output that occur during pregnancy. Although the echocardiographic findings did not show changes, it is suggested that there are changes related to increased blood volume in pregnancy to provide an appropriate blood flow to the conceptus. It was concluded that pregnancy and the postpartum period in bitches did not cause changes in electrolytes levels, SBP values, echocardiographic and electrocardiographic parameters as compared to values obtained during oestrus.